2016
DOI: 10.4025/actasciagron.v38i1.26045
|View full text |Cite
|
Sign up to set email alerts
|

<b>Interference of genotype-by-environment interaction in the selection of inbred lines of yellow melon in an agricultural center in Mossoró-Assu, Brazil

Abstract: ABSTRACT. The aims of this study were to i) identify the influence of the GxE interaction in the selection of inbred lines of melon, and ii) test the efficiency of different indexes in the selection of inbred lines with a higher yield potential and better quality fruit. For these purposes, 98 inbred lines of yellow melon and two commercial controls, Vereda and AF-646, were evaluated in a randomized block design with two replications, at the conditions present in Mossoró and Baraúna. Analyses of the following t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 11 publications
2
9
0
Order By: Relevance
“…In this case, the best options for selection were verified in groups 1 and 2 for productivity, and in group 2, for SS content, with estimates ≥60%. Estimates of heritability for productivity and SS content are within the ranges observed in some melon crops in the Mossoró-Assu Agricultural Complex (MELO et al, 2011;ARAGÃO et al, 2015, GUIMARÃES et al, 2016.…”
Section: Resultssupporting
confidence: 66%
See 3 more Smart Citations
“…In this case, the best options for selection were verified in groups 1 and 2 for productivity, and in group 2, for SS content, with estimates ≥60%. Estimates of heritability for productivity and SS content are within the ranges observed in some melon crops in the Mossoró-Assu Agricultural Complex (MELO et al, 2011;ARAGÃO et al, 2015, GUIMARÃES et al, 2016.…”
Section: Resultssupporting
confidence: 66%
“…This indicates that there was a predominance of the complex part of the interaction for the two traits evaluated, thereby making the selection process difficult. Previous studies in the Mossoró-Assu Agricultural Complex indicated the predominance of the complex interaction for productivity and SS content in Yellow melons (ARAGÃO et al, 2015;GUIMARÃES et al, 2016;NUNES et al, 2006;. Only Nunes et al (2011b) found a predominance of the simple part of the interaction when measuring SS content in Galia melon hybrids evaluated across nine environments in the Mossoró-Assu Agricultural Complex.…”
Section: Resultsmentioning
confidence: 88%
See 2 more Smart Citations
“…This is explained by the different response of genotypes to different environments (YAN et al, 2007). Genotype -environment interaction affects phenotypic manifestation and may hinder plant breeding and the recommendation of cultivars from the selection process (GUIMARÃES et al, 2016).…”
Section: Introductionmentioning
confidence: 99%